Cytotoxic and genotoxic effects of the trypanocidal drug diminazene aceturate. (January 2017) - Baldissera, Matheus; Sagrillo, Michele; Grando, Thirssa; Rosa, Luciana; Sá, Mariângela; Luz, Sônia; Silveira, Sergio; Nascimento, Kátia; Peres, Diulle; Copetti, Priscila; Silva, Aleksandro; Stefani, Lenita; et al.
Abstract Diminazene aceturate (D.A.) is an anti-parasitic drug that selectively targets adenine and thymine bases of deoxyribonucleic acid (DNA) of trypanosomes; however, there are some concerns regarding as its ability to induce DNA damage. Taking all of these into account, the aim of this study was to verify any possible toxic effects on the DNA of rats 7 and 21 post-injection (PI). All animals have received the therapeutic dose (single dose of 3.5 mg kg−1 ) intramuscularly. Liver, kidney, and total blood samples were collected to perform the analyses. The results showed increased (p  < 0.05) frequency of damage and damage index, as well as decreased (p  < 0.05) cell viability in liver and kidney of D.A. exposed rats on days 7 and 21 PI. Cytogenetic analyses in total blood demonstrated pyknotic nuclei, karyorrhexis, and karyolysis in D.A. exposed rats. reactive oxygen species (ROS) increased (p  < 0.05) in D.A. exposed rats on days 7 and 21 PI in liver and kidney samples, and a relationship between ROS production and cell damage was observed. Histopathology revealed vacuolar degeneration in both organs. Based on these results, we concluded that D.A. is cytotoxic and genotoxic to liver and kidney cells of rats due to increased ROS production when the therapeutic dose is used.